2014
DOI: 10.1177/1535370214561590
|View full text |Cite
|
Sign up to set email alerts
|

WWOX: A fragile tumor suppressor

Abstract: WWOX, the WW domain-containing oxidoreductase gene at chromosome region 16q23.3-q24.1, spanning chromosomal fragile site FRA16D, encodes the 46 kDa Wwox protein. WWOX is a tumor suppressor that is lost or reduced in expression in a wide variety of cancers, including breast, prostate, ovarian, and lung. The function of WWOX as a tumor suppressor implies that it serves an essential function in the prevention of carcinogenesis. Indeed, in vitro studies show that Wwox protein interacts with many binding partners t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 86 publications
0
41
0
Order By: Relevance
“…Our findings have important, broad therapeutic implications as Wwox is among the most commonly deleted genes in a wide variety of common human cancers 1,8,9,34 . We propose that determining Wwox expression levels could be an important predictor of response to radiation, cisplatin and possibly other chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 76%
“…Our findings have important, broad therapeutic implications as Wwox is among the most commonly deleted genes in a wide variety of common human cancers 1,8,9,34 . We propose that determining Wwox expression levels could be an important predictor of response to radiation, cisplatin and possibly other chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 76%
“…Here, we investigated whether tumor suppressor WW domain-containing oxidoreductase, known as WWOX, FOR, or WOX1, participates in the early signaling of T cell acute lymphoblastic leukemia (T-ALL) maturation. WWOX plays a crucial role in tumor suppression, metabolism, ataxia, epilepsy, neural disorders, neuronal damages and degeneration, and anti-viral immune responses (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Here, we showed that WWOX binds IB␣ and ERK and the complex localizes, in part, in the mitochondria of immature T lymphoid cells.…”
mentioning
confidence: 81%
“…Human WWOX gene has 1.1 million bases and is located on a chromosomal common fragile site 16q23 or FRA16D . High frequency of loss of heterozygosity (LOH) of WWOX gene at approximately 30–50% levels has been shown in many types of cancer cells (Aqeilan and Croce, 2007; Chang et al, 2007; Del Mare et al, 2009; Gardenswartz and Aqeilan, 2014; Abu-Remaileh et al, 2015; Chang, 2015; Chang et al, 2015; Richards et al, 2015; Schrock and Huebner, 2015). Mutation of WWOX gene in breast cancer occurs frequently at exons 4–9 (Ekizoglu et al, 2012).…”
Section: Tumor Suppressor Wwox Is Anchored On the Cell Membrane By Hymentioning
confidence: 99%
“…Second, functional deficiency or defect of the HYAL-2-WWOX-SMAD4 signaling complex may occur in cancer cells. For example, tumor suppressor WWOX is frequently missing in cancer cells (Bednarek et al, 2000; Chang et al, 2001, 2003, 2007; Iliopoulos et al, 2005; Aqeilan and Croce, 2007; Chiang et al, 2013; Gardenswartz and Aqeilan, 2014; Abu-Remaileh et al, 2015; Schrock and Huebner, 2015; Huang et al, 2016). Lastly, the CD44-HYAL-2 complex provides spatial hindrance for the binding of TGF-β1 with Hyal-2.…”
Section: Hyal-2 Is a Cognate Receptor For Tgf-β: Signaling Via Hyal-2mentioning
confidence: 99%